Шпионами не рождаются - Атаманенко Игорь Григорьевич (ЭКСМО- Пресс, 2000)
Экземпляры: ф.6 (20171213) / Инвентарный номер: 2205 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 92 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44